Quantifying Turkana’s wild edible plants’ contribution to critical micronutrient and dietary diversity among women of reproductive age - Oduor, Francis; Keding, Gudrun; Kaindi, Dasel Mulwa; Abong, George; Thuita, Faith; Termote, Celine (Informa UK Limited, 2024)
This study explored wild edible plants' (WEPs) contribution to dietary diversity and micronutrient intakes of women in Turkana County using a multi-method quantitative research design. In addition to the nutrient composition analysis of four vegetable plants and one edible fruit collected from the wild, two survey rounds were conducted – in 2020 during COVID (n = 360) and in 2022 during extreme drought (n = 600), to collect dietary intake data of women using 24-h recall. The study revealed that WEPs contribute 12% to 30% of the total daily food intake among women, and 0.6 to 1.4 food groups to dietary diversity, depending on the season. All the five WEPs tested contained on average 0.5 mg zinc, 6.4–25.5 mg iron, and 97.8–330.8 mg calcium per 100 g edible portion. This study demonstrates the significance of WEPs' nutritional contribution to the Turkana communities' diets, and their pivotal role during times of food scarcity, and recommends their promotion alongside measures to prevent their overexploitation.